DESAIN SARANA BAWA LAPTOP DAN ALAT KOMUNIKASI (SMARTPHONE, TABLET) DENGAN ELEMEN ESTETIS BERTEMA ETNIK KAIN TRADISIONAL - Royke Vincentius; Fahry Noor Anshori (Jurnal Kreatif : Desain Produk Industri dan Arsitektur, 2017)
Gadgets are terms that come from English, which means small software that has special functionality. It is undeniable that technology is growing rapidly and in human nostalgia. Generally people carry gadgets using ordinary bags. Bag gadgets are now there yanng using cultural elements in Indonesia but still use batik cloth on bags that have been widely used. Because iu, the author wants to make “Means of Bringing Laptops and Electronic Devices (Smartphone, Tablet) With Aesthetic Elements Themed Traditional Ethnic Cloth”. The design method that is done is observation, problem formulation, literature study, analysis, design and alternative design, development of selected design, modeling, drawing and prototype. For that with the “Means Bring Laptops and Electronic Devices (Smartphone, Tablet) With Aesthetic Elements Ethnic Traditional Cloth”. Users can carry and store gadgets, with a more ergonomic design, and aesthetically nuanced. The bag is equipped with a neat and orderly configuration, and prioritizes comfort and security for the user when using the bag.